The Effectiveness of Emotionally Focused Couple Therapy on Self-Differentiation and Intolerance of Uncertainty in Couples Seeking Divorce - Saniei, Sahar; Hasanzadeh, Hosein; Hosseinzadeh, Shima; Eslami, Narjes; Nasri, Maryam; Pourmohammadghouchani, Kamran (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the effectiveness of Emotionally Focused Couple Therapy (EFCT) on differentiation of self and the reduction of intolerance of uncertainty in couples seeking divorce. Methods: The research method was quasi-experimental with a pretest–posttest control group design. The statistical population consisted of couples seeking divorce in Tehran, from which 30 couples were selected through convenience sampling and randomly assigned to experimental and control groups. The experimental group underwent a 10-session EFCT intervention, each session lasting 90 minutes, while the control group did not receive any intervention. Findings: Findings showed that Emotionally Focused Couple Therapy significantly increased differentiation of self and reduced intolerance of uncertainty in couples seeking divorce. Conclusion: These results suggest that by focusing on core emotions and emotional interactions, it is possible to improve interpersonal relationships and facilitate more informed decision-making in marital relationships. Accordingly, the use of EFCT is recommended in psychological interventions related to divorce crises.